2015
DOI: 10.1371/journal.pone.0145930
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-197 and miRNA-223 Predict Cardiovascular Death in a Cohort of Patients with Symptomatic Coronary Artery Disease

Abstract: BackgroundCirculating microRNAs (miRNAs) have been described as potential diagnostic biomarkers in cardiovascular disease and in particular, coronary artery disease (CAD). Few studies were undertaken to perform analyses with regard to risk stratification of future cardiovascular events. miR-126, miR-197 and miR-223 are involved in endovascular inflammation and platelet activation and have been described as biomarkers in the diagnosis of CAD. They were identified in a prospective study in relation to future myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 35 publications
4
118
0
3
Order By: Relevance
“…The group identified miR-126, miR-197, and miR-223 to reliably predict future MI in 820 individuals from the Bruneck study [97] (for further details on the Bruneck study, see [31]). These results were recently validated [98] by identifiying miR-197 and miR-223, as well as miR-126, as strong predictors of cardiovascular death in a large cohort of 873 patients with invasively diagnosed CAD [98]. These results not only transfer the diagnostic potential of miRNAs in CVD to a prognostic level, they also indicate the promising applicability of miRNAs as useful biomarkers in primary and secondary prevention in CVD.…”
Section: Mirnas In Prediction and Prognosis Of Coronary Artery Diseasmentioning
confidence: 73%
“…The group identified miR-126, miR-197, and miR-223 to reliably predict future MI in 820 individuals from the Bruneck study [97] (for further details on the Bruneck study, see [31]). These results were recently validated [98] by identifiying miR-197 and miR-223, as well as miR-126, as strong predictors of cardiovascular death in a large cohort of 873 patients with invasively diagnosed CAD [98]. These results not only transfer the diagnostic potential of miRNAs in CVD to a prognostic level, they also indicate the promising applicability of miRNAs as useful biomarkers in primary and secondary prevention in CVD.…”
Section: Mirnas In Prediction and Prognosis Of Coronary Artery Diseasmentioning
confidence: 73%
“…Oerlemans et al 74 revealed that the combination of miR-1, miR-21 and miR-499 had a higher diagnostic value than hs-troponin T. In addition to diagnostic value, miRNAs may be more useful for risk stratification and can be used as prognostic biomarkers 75. Circulating miRNA-197 and miRNA-223 were identified as predictors for cardiovascular death in a large patient cohort with coronary artery disease 76. Studies also found that miRNA-134, miRNA-328, miRNA-34a and miRNA-208b were associated with the development of heart failure and increased risk of mortality after AMI 77 78…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…Additional studies revealed that miR-223 directly targets SR-B1, HMGCS1, and methylsterol monooxygenase 1(SC4MOL) for modulation of HDL-C uptake and cholesterol biosynthesis 102 . The finding that miR-223 is elevated in CAD patient’s serum 103 adds a layer of complexity to the role of miR-223 in the pathogenesis of CAD. One explanation is that miR-223 has pleiotropic physiologic roles thus, its upregulation in serum may serve as a biomarker of disease or compensatory mechanism rather than a direct modulator of the pathophysiology of disease.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%